2018
DOI: 10.1098/rsos.171503
|View full text |Cite
|
Sign up to set email alerts
|

Differential arthropod responses to warming are altering the structure of Arctic communities

Abstract: The Arctic is experiencing some of the fastest rates of warming on the planet. Although many studies have documented responses to such warming by individual species, the idiosyncratic nature of these findings has prevented us from extrapolating them to community-level predictions. Here, we leverage the availability of a long-term dataset from Zackenberg, Greenland (593 700 specimens collected between 1996 and 2014), to investigate how climate parameters influence the abundance of different arthropod groups and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 123 publications
5
73
0
Order By: Relevance
“…In contrast to other areas of high‐arctic tundra, vegetation structure at our study area of Zackenberg has been relatively stable so far (IPCC, ; Schmidt, Kristensen, Michelsen, & Bay, ). Yet, the area has experienced changes in flower phenology, soil moisture and air temperature in the last 19 years, leading to a decline in muscid flies and Collembola but to an increase in Hemiptera and parasitoid wasps (Høye et al., ; Koltz et al., ; Loboda et al., ). The availability of the most important prey of Pardosa —chironomid and culicid midges—may perhaps be less affected by climate change due to the buffered, aquatic habitat of their larvae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other areas of high‐arctic tundra, vegetation structure at our study area of Zackenberg has been relatively stable so far (IPCC, ; Schmidt, Kristensen, Michelsen, & Bay, ). Yet, the area has experienced changes in flower phenology, soil moisture and air temperature in the last 19 years, leading to a decline in muscid flies and Collembola but to an increase in Hemiptera and parasitoid wasps (Høye et al., ; Koltz et al., ; Loboda et al., ). The availability of the most important prey of Pardosa —chironomid and culicid midges—may perhaps be less affected by climate change due to the buffered, aquatic habitat of their larvae.…”
Section: Discussionmentioning
confidence: 99%
“…For this, we use an altitudinal gradient in the High Arctic and examine how the environment, species traits and phylogenetic relationships shape trophic interactions. In the arctic biome, recent research has revealed an increase in temperature and humidity (Bintanja & Andry, 2017;IPCC, 2013), increased plant biomass and extension of shrubs and subsequent changes in arthropod abundances and community composition (Bowden, Hansen, Olsen, Schmidt, & Høye, 2018;Høye, Post, Schmidt, Trøjelsgaard, & Forchhammer, 2013;Koltz, Schmidt, & Høye, 2018;Loboda, Savage, Buddle, Schmidt, & Høye, 2018). Importantly, the very same parameters vary along our elevational gradient, emphasizing the space-for-time connection (IPCC, 2013).…”
mentioning
confidence: 99%
“…In this case, winter precipitation has a negative association with moth abundance, while winter temperature has a positive association (28). In Greenland, changes in the structure of arthropod communities over 18 years have been influenced by warming summers and falls and fewer freeze-thaw events, with the most negative associations observed for surface detritivores (29). On the other side of the temperature spectrum is maximum temperature, which has been shown to be the variable most associated with local extinctions in a global survey of insects and other taxa (18).…”
Section: On Changing Maximums Minimums Means and Variancementioning
confidence: 99%
“…Our previous work on spiders (Araneae) and a single family of flies (Diptera) has shown that habitat type can play an important role in the strength of species abundance trends (16, 28, 29). Previously, we also found evidence of differential long-term changes across invertebrate orders, altering the entire community composition (30). Therefore, there is an urgent need for an improved understanding of the spatial and taxonomic variation in population dynamics of arthropods.…”
Section: Introductionmentioning
confidence: 53%